A study on the factors influencing employee’s satisfactions towards the organizational benefits / Nurul Syafiqah Mohammad Fahimi and Syazwani Mohd Shatir - Mohammad Fahimi, Nurul Syafiqah; Mohd Shatir, Syazwani (2018)
This study is to focus on benefits from organization to the employees at hotel industry. Organization benefits are benefits offered to employees from employers, such as good working environment, pay and promotion and a retirement plan. Then, offering organization benefits can shape a company’s culture and affect employee retention. A set of positive and negative feelings that an employee have about his job is also known as employee’s satisfaction. So, this study is to examine the factors influencing of the employee’s satisfaction on organization benefits a study of five star hotel in Kedah. This was focusing at five-star Grand Alora Hotel, Alor Setar, Kedah. A descriptive research design was used in the study. The target population was 132 employees of five-star hotels in Grand Alora Hotel, Alor Setar, Kedah. Census technique was used to determine the sample size. Primary data was collected using a structured questionnaire. Statistical Package for Social Sciences (SPSS) is to ensure good quality of the data. Cronbach alpha was used to determine reliability of the questionnaire and correlation analysis was done to determine the relationship between dependent and independent variables. Findings revealed that there was a strong positive relationship between financial rewards, working condition, employer commitment. The study concluded there is a clear evidence that five stars hotels in Grand Alora Hotel, Alor Setar, uses various forms of employees financial rewards such as allowances as recognition strategy to show the value of employees at work. It can also be concluded that working condition enhance employees satisfaction and productivity. The employer commitment also can lead to increase the level employee satisfaction towards the organization benefits. Moreover, from the findings the most factor that influence the employee’s satisfaction toward organization benefits is financial rewards.